How Not to Link the Reformation and Science: Reflections on Brad Gregory's The Unintended Reformation - Reeves, Josh A. (Religions, 2017)
This article evaluates Brad Gregory's argument in The Unintended Reformation that links the Reformation with the rise of secular science. I provide an overview of Gregory's claims and make two criticisms, arguing that Gregory's thesis lacks historical evidence to support it and mistakenly implies that retaining the framework of premodern metaphysics would have prevented the rise of scientific naturalism. The paper concludes by pointing to more positive accounts on the connection between the Reformation and science by recent historians.